The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1361-6528/ab996f
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite of Ag nanoparticles and catalytic fluorescent carbon dots for synergistic bactericidal activity through enhanced reactive oxygen species generation

Abstract: Microwave mediated synthesis of catalytic fluorescent carbon dots (Cdots) has been reported using biodegradable starch as precursor. The as-synthesized Cdots were then characterized using various techniques such as fluorescence spectroscopy, fourier-transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM) and x-ray photoelectron spectroscopy (XPS) analysis. Interestingly, Cdots showed high catalytic activity in the photo-reduction of Ag+ to silver nanoparticles (Ag NPs). During the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Therefore, it is meaningful to use synthetic bimetallic MOF materials to inhibit bacterial growth. The growth curves of E. coli and S. aureus under normal conditions clearly show four periods of bacterial growth: delayed, logarithmic, stable, and decaying periods [ 51 , 52 , 53 , 54 , 55 ]. The progressive decrease in the logarithmic phase for different concentrations of MIL-101(Fe)@Ag (Ag 0.0127 wt%) (60, 80, 100 and 120 μg/mL), along with the decrease in the time for the bacteria to reach the plateau phase ( Figure 12 a,b), indicated that the inhibition of E. coli and S. aureus by MIL-101(Fe)@Ag (Ag 0.0127 wt%) was concentration-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is meaningful to use synthetic bimetallic MOF materials to inhibit bacterial growth. The growth curves of E. coli and S. aureus under normal conditions clearly show four periods of bacterial growth: delayed, logarithmic, stable, and decaying periods [ 51 , 52 , 53 , 54 , 55 ]. The progressive decrease in the logarithmic phase for different concentrations of MIL-101(Fe)@Ag (Ag 0.0127 wt%) (60, 80, 100 and 120 μg/mL), along with the decrease in the time for the bacteria to reach the plateau phase ( Figure 12 a,b), indicated that the inhibition of E. coli and S. aureus by MIL-101(Fe)@Ag (Ag 0.0127 wt%) was concentration-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, CDs play an important role in reducing silver ions and stabilizing the nanoparticles, the addition of fluorescent CDs to silver nanoparticles can increase the negative surface charge and hydrophilicity. 30 Meanwhile, the fluorescent CDs could be quenched by silver nanoparticles due to their proximity, resulting in surface plasmon enhanced energy transfer from CDs to AgNPs. 31 Currently, a great deal of effort has been put into the synthetic process of CDs/AgNPs composite, however, a series of reducing agents, such as sodium borohydride, sodium citrate, citric acid and so on, are still used to assist in reducing silver ions.…”
Section: Introductionmentioning
confidence: 99%
“…The use of biodegradable starch as precursor has been documented by Verma et al, using microwave-controlled synthesis of catalytic fluorescent carbon dots. The synthesized C-dots demonstrated catalytic activity in the Ag NPs' photo-reduction [185]. This treatment of Ag NPs and C-dots has been observed to be highly bactericidal, with substantially low silver concentration compared to Ag NPs.…”
Section: Hetero Atomic Dopingmentioning
confidence: 96%